Butyrate rather than LPS subverts gingival epithelial homeostasis by downregulation of intercellular junctions and triggering pyroptosis. (14th August 2019) - Liu, Juan; Wang, Yixiang; Meng, Huanxin; Yu, Jingting; Lu, Hongye; Li, Wenjing; Lu, Ruifang; Zhao, Yibing; Li, Qiqiang; Su, Li
Abstract: Aim: To investigate the effects of sodium butyrate (NaB) and lipopolysaccharide (LPS) on gingival epithelial barrier. Material and methods: We cultured human primary gingival epithelial cells and investigated the effects of NaB and LPS on gingival epithelial barrier and involved mechanisms at in vitro and in vivo levels by immunostaining, confocal microscopy, field emission scanning electron microscopy (FE‐SEM), transmission electronic microscopy (TEM), transepithelial electrical resistance (TEER), FTIC‐dextran flux, flow cytometry, real‐time PCR and Western blot assays. Results: Our results showed that NaB, rather than LPS, destroyed the epithelial barrier by breaking down cell–cell junctions and triggering gingival epithelial cell pyroptosis with characteristic morphological changes, including swollen cells, large bubbles, pore formation in the plasma membrane and subcellular organelles changes. The upregulated expression of pyroptosis‐related markers, caspase‐3 and gasdermin‐E (GSDME) contributed to this effect. Pyroptosis aroused by NaB is a pro‐inflammatory cell death. Pyroptotic cell death provoked inflammatory responses by upregulation of IL‐8 and MCP‐1, and releasing intracellular contents into the extracellular microenvironment after pyroptotic rupture of the plasma membrane. Conclusions: Our new findings indicate that butyrate is a potent destructive factor of gingival epithelial barrier and pro‐inflammatory mediator, which shed a new light on our understanding of periodontitis initiation.